The liberation of women in Islam between reality and practice in Arab society - Najmiah, Omar (2020)
At a time when women were living in the worst times of human injustice, in a world filled with myths and delusions, and female infanticide considering her a commodity that is sold, bought, and conferred, depriving them of inheritance, class racism and ethnic discrimination, religious beliefs and texts that criminalize and describe them as Satan and put them in a state of complete servitude to man’s injustice whims and desires. Islam came to liberate her from those unjust beliefs and practices, and restored her position and gave her rights, which are inherent rights that God gave her, not a favor or favored by anyone, but they are the rights of every woman, without discriminating between sex to another, color to color, and rich to poor society that it is oppressed and has no right, therefore they are also equalized rights to those who live in a cottage with those who reside in the skyscrapers, both .This research aims to shed light on the most important and prominent topics for the liberation of women in Islam and the gap in the application in the contemporary time because of the dimension and the ignorance of the religion and unfiltered cultural openness .In this research, I used the descriptive analytical approach to analyze the sharia texts and statements of some scholars in this matter, and the actual application or lack thereof in reality. In addition, I also discussed and touched on the great outcomes of what Islam presented to women and its distinction as a divine system and approach from all previous and subsequent systems, and the differences of this approach and the way it is applied and understood in the reality of the Islamic societies.